Vaccine strategies to induce broadly protective immunity to rhinoviruses - McLean, Gary R. (Hum Vaccin Immunother, 2019)
Rhinoviruses are ubiquitous human pathogens of the upper respiratory tract and are the major cause of acute exacerbations of asthma and chronic obstructive pulmonary disease. At least 160 antigenically distinct serotypes or strains have been identified and protective immunity is largely serotype specific. Attempts to produce vaccines that induce broad immunity have met with limited success which is due in part to this antigenic diversity and a lack of information regarding the ideal protective immune responses. Recent approaches identifying conserved rhinovirus epitopes and better definitions of the immune correlates of protection have raised hope. Here, these newer findings are outlined and the prospects for such a universal rhinovirus vaccine are discussed.